Estimation of direct medical cost related to the management of chronic hepatitis C and its complications in South Korea. Issue 30 (July 2016) - Kim, Do Young; Yoon, Ki Tae; Kim, Won; Lee, Jung Il; Hong, Sung Hwi; Lee, Danbi; Jang, Jeong Won; Choi, Jong Won; Kim, Ilsu; Paik, Yong Han
Abstract: Background: This study aimed to estimate the direct medical costs of managing chronic hepatitis C (CHC) and its complications based on health-care resources in South Korea. Methods: The study design was multicenter, retrospective, non-interventional, and observational. Between September 2013 and April 2014, health-care resource data from patients chronically infected with hepatitis C virus, regardless of genotype, were collected from 8 institutions, including data related to outpatient management, emergency care, and hospitalization. The observation period was between January 2011 and December 2012. The disease state was classified as CHC, compensated cirrhosis (CC), decompensated cirrhosis (DC), or hepatocellular carcinoma (HCC). Results: A total of 445 patients were recruited and mean age was 60.1 ± 12.3 years. Among 155 patients with reported outcomes of antiviral therapy, 107 (69%) had sustained virologic response (SVR). The rate of patients who did not receive antiviral therapy was 52.8% (n = 235). The distribution of disease state was CHC in 307 patients (69.0%), CC in 75 (16.9%), HCC in 45 (10.1%), and DC in 18 (4.0%). All direct medical costs, whether reimbursed or nonreimbursed by the National Health Insurance System, were included. After excluding patients whose observational period was <1 month for each disease status, the mean costs per month increased as disease state progressed (CHC: 77 ± 80 USD; CC: 98 ± 94 USD; DC: 512 ± 1115 USD; HCC: 504 ± 717 USD). The mean total costs per person were 3590 ± 8783 USD, and approximately 72% of patients were reimbursed. When 44 patients with an observation period <1 month were excluded, the mean medical costs per month for patients with CHC who achieved SVR (n = 69) were significantly lower than for those (n = 215) who did not (42 ± 16 vs 79 ± 83 USD, P  < 0.001). The cost also tended to be lower for patients with CC with SVR (n = 8) than for those without SVR (n = 70; 48 ± 20 vs 95 ± 96 USD, P  = 0.177). The cost of antiviral therapy (pegylated interferon and ribavirin) corresponded to 19.0% of total medical costs and 53.7% of prescription/pharmacy. Conclusion: The direct medical costs increased as disease state progressed from CHC to cirrhosis or HCC. The achievement of SVR by antiviral therapy would decrease the costs.